EFFECTS OF TOTAL RESISTANCE EXERCISE AND DYNAMIC STRETCHING ON ENERGY EXPENDITURE AND CRAWL STROKE SPEED IN YOUNG SWIMMERS - Sittichai Pengkumpa,; Kurusart Konharn, (Sport Scientific And Practical Aspects, 2025)
Warm-up, stretching in exercise and training is important to swimmers. TRX enhances muscle nervous functions, while dynamic stretching have a positive effect on the body’s structural strength, flexibility, body balance, stability, and range of motion. Therefore this study was purposed to measure the effects of TRX and dynamic stretching on energy expenditure and crawl stroke speed in young swimmers. Participants (aged 12.46 ± 0.29 years, BMI 19.51±3.59 kg/m2) received two warm-up programs separated by a week’s resting interval. First, a conventional warm-up with TRX for 30 minutes, in the second, they participated in 30 minutes of conventional warm-up with dynamic. After 10 minutes of rest they were tested on their 50-meter crawl stroke speed. Female swimmers received conventional warm-up with dynamic had a better crawl stroke speed than male swimmers (36.49 ± 1.45 vs. 38.36 ± 4.77 seconds). Male swimmers received conventional warm-up with TRX had a faster crawl stroke speed than female swimmers (36.43 ± 4.17 vs. 38.53 ± 1.32 seconds, respectively, p<0.05). A conventional warm-up with TRX showed less energy expenditure than dynamic (47.48 ± 20.89 vs. 32.02 ± 8.82 cal, respectively, p<0.05). Conventional warm-up with TRX used less energy than dynamic group (14.11 ± 3.82 vs. 12.44 ± 3.36 KJ, respectively, p<0.05). Therefore conventional warm-up with TRX and dynamic enhance crawl stroke speed than a conventional warm-up, which may be an appropriate method to augment speed in young swimmers.